IMPLEMENTATION OF CLASSICAL GUIDANCE SERVICES BASED ON PROBLEM BASED LEARNING TO IMPROVE CLEAN AND HEALTHY LIVING BEHAVIORS OF HIGH SCHOOL STUDENTS - Kevin, Mohamad; Noory, Diaz Muhammad; Safina, Fathia Alida; Dimas, Muhamad; Afiati, Evi (Universitas Dharmawangsa Medan, 2025)
AbstractThis reserach aims to analyze student needs through the Student Needs Questionnaire (AKPD) and to design classical guidance services on the topic of Clean and Healthy Living (PHBS) in class X-1 at SMAN 1 Baros. This study uses a qualitative approach involving observation and interviews. Based on the results of the AKPD analysis of 33 respondents, it was found that 38.03% of the problems were in the personal domain, particularly related to a lack of understanding of maintaining personal health. This shows the urgency of developing basic counseling services that are preventive in nature with the aim of increasing students' awareness of the importance of PHBS. The service methods used were Problem-Based Learning (PBL) and the Korogaru Bidama educational game to increase interactivity. The results of the implementation showed that students were able to identify the benefits of PHBS, change their behavior to be healthier, and design simple programs related to healthy living habits. This article contributes to strengthening preventive counseling services based on the real needs of students, while also emphasizing the important role of guidance counselors in supporting the formation of healthy character in students.